Does tax competition make tax reform essential? - Maja Klun (Central European Public Administration Review)
Tax competition is generally defined as competition between national economies to increase their competitiveness and attract foreign investment by means of tax policy. Tax policy measures that tax mobile or foreign capital at significantly lower rates are known as harmful tax competition. Some recent corrections to the tax code and proposed tax amendments in Slovenia represent an attempt to relieve the burden on the taxpayer. This paper compares the taxation of high income taxpayers, low income taxpayers, taxpayers with passive income, and the taxation of businesses in Slovenia and neighbouring countries. The comparison indicates that Slovenian taxpayers with a high income have a higher tax burden than in neighbouring countries, while low income taxpayers have one of the highest burdens. The same applies to passive income. The tax burden on businesses ranks in the middle.